Synthetic studies towards bistramide D - Kalpana Palani (2010)
Bistramide D is a member of new class of bioactive molecule isolated from the marine ascidian Lissoclinum bistratum in New Caledonia. Bistramides (A, B, C, D and K) show a broad spectrum of biological activity which includes antiproliferative, immunomodulatory, neurotoxic, cytotoxic and antiparasitic properties; the recent studies also show that bistramides bind to Actin. Bistramide A was reported to be very potent for the P388/dox, B16, HT29, and NSCLC-N6 cell lines. Bistramide D has similar activity in the NSCLC-N6 cell line but is comparatively less toxic in vivo. There has been no total synthesis of bistramide D reported till now to our knowledge. These intriguing biological profiles and challenging molecular architecture of bistramides motivated us to synthesize bistramide D.